Cybercrime as a Modern Threat to Military Security - AZHIBAYEV, Marat G.; DZHANADILOV, Olzhas M. (Journal of Advanced Research in Law and Economics; Vol 9 No 5 (2018): JARLE Volume IX Issue 5(35) Fall 2018, 2018)
Crime does not stand still and evolves with humanity. With the development of technologies, new types of crimes have appeared and, accordingly, new threats that today challenge not only an individual, but entire states, creating risks of harm not only to the economic sector, but to military and national security in general. At the same time, it is important that cybercrime in the field of military security can cause harm to the entire defense complex of the country, leaving the state defenseless against other threats which is unacceptable in order to preserve the sovereignty and the independence of the young democratic state. In this connection, it is necessary to recognize cybercrime at the state level as a threat that could cause harm to military security.